COVID-19 pandemic and its impact on dental education: digitalization - progress or regress? Example of an online hands-on course - Oetter, Nicolai; Möst, Tobias; Weber, Manuel; Buchbender, Mayte; Rohde, Maximilian; Foerster, Yannick; Bauerschmitz, Charlotte; Röschmann, Nico; Adler, Werner; Rau, Andrea; Meyerolbersleben, Marion; Kesting, Marco Rainer; et al. (BMC Medical Education, 2022)
BACKGROUND: Due to the SARS-CoV-2 pandemic and the accompanying contact restrictions, a new challenge arose for dental education. Despite the limited overall situation, it must be ensured that, in addition to theoretical content, practical skills in particular continue to be taught. Therefore, the aim of this study was to develop and implement an online hands-on course for dental students that ensures practical training, even during the pandemic. METHODS: The newly developed course was held from April 2020 to March 2021. A total of six groups (each consisting of approximately 40-50 students) took part in the course. The participating students were in their 3rd, 4th or 5th year of study. The course taught theoretical basics (via an online platform) and promoted the learning of practical/surgical techniques on models such as bananas, pork bellies, or chicken thighs with live demonstrations (via ZOOM) and interactive post-preparation by students at home (and in a rotating small group of 3-7 students on site). Student self-evaluation (at the beginning and end of the course) and course evaluation were performed using questionnaires. The learning success was analyzed (through self-evaluations) using Wilcoxon signed-rank tests (significance level alpha = 0.05). RESULTS: Concerning students´ self-evaluations, the theoretical knowledge, general surgical skills (such as surgical instrument handling), and specific surgical skills (such as performing a kite flap) improved during the course, with significant results (p < 0.001 for each). About 60% of the students rated the course overall as excellent (grades 9 or 10 on a Likert scale of 1 to 10). The technical implementation of the course was rated with a median of 9 (= very good, on a Likert scale of 1 to 10). 38.5% described the applicability of the skills learned for their later professional life as extremely good. CONCLUSIONS: The results of this work suggest that, within the limitations of this study, the introduced concept of an online hands-on course could be an appropriate form of teaching practical dental skills, even during a pandemic. Further research is needed in the field of digital education for dental students.
Created from Fastlane, Scopus look-up
Keywords: Asynchronous; Coronavirus; Dentistry; Digital; Education; Pandemic; Synchronous

Development of a digital Teaching Project on the Topic of "Immunooncology" - Kaufmann, Matthias; Berking, Carola; French, L. E.; Meyerolbersleben, Marion; Reinholz, M.; Steeb, Theresa; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Does it just have something to do with Age? Conceptual Gaps between Paradigms of Child and Adult Psychosomatics based on new Data from the "Prien Study on Values, Goals and Stress Experiences of mentally ill Adolescents" - Hillert, Sophia; Meyerolbersleben, Marion; Naab, Silke (ZEITSCHRIFT FUR PSYCHOSOMATISCHE MEDIZIN UND PSYCHOTHERAPIE, 2019)
CRIS-Team WoS Importer:2020-03-17

eImmunonkologie: Development and Launch of a Virtual Education Platform for the Immunotherapy of Cutaneous Neoplasms - Kaufmann, Matthias; Steeb, Theresa; Wessely, Anja; Meyerolbersleben, Marion; French, Lars E. E.; Berking, Carola; Heppt, Markus (Medical Science Educator, 2022)
The use of immunotherapies in clinical practice has significantly expanded treatment options and improved the prognosis of patients with advanced cancers over the past decade. We have developed a virtual teaching module entitled "eImmunonkologie" which is the first interdisciplinary virtual course on immuno-oncology for medical students in German-speaking countries.
CRIS-Team WoS Importer:2023-01-20

Was brauchen Burn-out-Kids? - Werte, Ziele und Belastungserleben von gesunden und psychosomatisch erkrankten Jugendlichen - Meyerolbersleben, Marion; Hillert, Andreas; Naab, Silke; et al. (Psychische Gesundheit wirksam stärken - aber wie?, 2020)
Psychische Störungen bei Jugendlichen haben in den vergangenen Jahrzehnten zugenommen. Viele Jugendliche erleben eine hohe Stressbelastung, nicht wenige fühlen sich ausgebrannt. Ausgehend von Untersuchungen gesunder und psychisch erkrankter Jugendlicher geht dieser Beitrag der Frage nach, auf welche Weise belasteten Jugendlichen am besten geholfen werden kann. Entgegen der häufig geäußerten Vermutung, wonach Jugendliche möglichst "nicht unter Druck" gesetzt und entlastet werden sollen, erleben sich gerade die Maximal entlasteten Jugendlichen, also diejenigen, die keine konkreten beruflichen Ziele haben und "Spaß im Beruf" als zentralen Wert im Leben angeben, als die erschöpfteste und in diesem Sinne belastetste Gruppe. Die folgenden Auswertungen zeigen: Weniger Entlastung und stattdessen eine Realitätsanpassung und Konkretisierung von Werten und Zielen sind notwendig, um die psychische Gesundheit von Jugendlichen wirksam zu stärke
Keywords: Burnout; Werte; Jugendliche; Burn-out; psychische Störung; ausgebrannt; psychische Gesundheit